Influence of H2C204 solution on formation of Porous AAO thin film - Puteri Normiyani Abu Hassan (Universiti Malaysia Perlis, 2008)
The anodizing of aluminium has been investigated with the aim to realize nano-porous structures and nano-porous oxides for use as nano-templates. Before undergoing electrochemical oxidation, aluminium samples were cleaned in acetone, annealed at 450ºC under nitrogen flow. Then the Al sheets undergo alkaline etching in NaOH at 50 ºC to 60ºC and dipped in HNO3 at room temperature. Anodizing was carried out using oxalic acid, H2C2O4 as electrolyte. Different combinations of processing parameters (anodization time, electrolyte concentration, and current density) were used in order to optimize the process. The phase analysis of the samples was analyzed by X-Ray Diffraction (XRD) and the porous surface was observed by Scanning Electron Microscopy (SEM). The results show that at lower current density and short anodizing time, no pores were formed in each different electrolyte concentration. However, increasing the anodizing time to 2 hours produced smaller, rounded pores. But at short anodizing time with higher current density produced bigger pores. The pores formed were not uniformly distributed. Further investigations are required to optimise the production of highly self-ordered porous structures. By optimizing all of these experimental conditions, we were able to obtain porous anodic aluminum oxide layers displaying ordered domains several hundreds of nanometers in length.